2017
DOI: 10.3233/isu-170821
|View full text |Cite
|
Sign up to set email alerts
|

Libraries and librarians: Key partners for progress in health literacy research and practice

Abstract: The field of librarianship has a history of involvement in patient education, general literacy and information literacy efforts. This history and prominent placement in communities make libraries and librarians an excellent resource in advancing health literacy practice and research. This chapter provides an overview of health literacy and health information literacy efforts in US libraries over the past two decades.The chapter begins with the description of the role of the US National Library of Medicine in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
0
28
0
2
Order By: Relevance
“…Since libraries are essentially the hub of data and information, several research findings and reports find their way into the library or are accessible to librarians. Libraries can leverage on this strength to monitor the progress of SDG‐3 using available data to measure the 13 targets of the ‘good health’ goal, in line with health literacy research reported in the literature (Whitney et al., ; Zach et al., ). Libraries can use this to monitor how their country is doing in terms of achieving the goal.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Since libraries are essentially the hub of data and information, several research findings and reports find their way into the library or are accessible to librarians. Libraries can leverage on this strength to monitor the progress of SDG‐3 using available data to measure the 13 targets of the ‘good health’ goal, in line with health literacy research reported in the literature (Whitney et al., ; Zach et al., ). Libraries can use this to monitor how their country is doing in terms of achieving the goal.…”
Section: Discussionmentioning
confidence: 90%
“…Librarians have engaged in health literacy research to document information resources, access, services, training needs, challenges and information behaviour of users (Whitney, Keselman & Humphreys, ). Some health literacy research also evaluate health literacy interventions (Xie, ; Zach, Dalrymple, Rogers & Williver‐Farr, ), while librarians’ health literacy was also a subject of research (Amini & Mostafavizade, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Libraries are a natural place for community members to get access to the wide range of information available, and to seek assistance from librarians to support lifelong learning and skill development. Long before the term "health literacy" was applied to this area, librarians actively answered consumer health questions and provided patient education (Whitney et al, 2017). Librarians know their local communities and can engage people and connect them to resources.…”
Section: Roles For Librarians and Other Information Professionalsmentioning
confidence: 99%
“…The program was piloted in 16 Pennsylvania public libraries and the toolkit is freely available for other libraries to use in their communities (National Network of Libraries of Medicine, 2017). In June 2013, attendees at the American Library Association were called to action by President Barack Obama to support the public's health information needs and assist with signing up for health insurance on the online marketplace created by the ACA (Whitney et al, 2017). Public libraries met the call with varying capacities for support, with very few (only 5%) thinking they should not play a role in the ACA (Kohn, 2013).…”
Section: Public Librariesmentioning
confidence: 99%